Cooperación Para El Desarrollo Cultural - Canelas Rubim, Antonio Albino (Re-presentaciones: Periodismo, comunicación y sociedad, 2007)
In an epoch of globalization and accelerated interaction, like the present time, it has more sense to think about the value of communication and its impact on sociability. The contemporary world is one of connections, interactions and networks. There are at least two ways of connection: imposition or cooperation. This paper is an advance towards the description of cooperation connections applied to the cultural field.